P38 Signaling Pathway - Cuenda, Ana; Sanz Ezquerro, Juan José (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
p38 Mitogen activated protein kinases (p38MAPK) are a group of evolutionary conserved protein kinases which are central for cell adaptation to environmental changes as well as for immune response, inflammation, tissue regeneration and tumour formation. The interest in this group of protein kinases has grown continually since their discovery. Recent studies using new genetic and pharmacological tools are providing helpful information on the function of these stress-activated protein kinases and show that they have an acute impact on the development of prevalent diseases related to inflammation, diabetes, neurodegeneration, and cancer. In this Special Issue we present novel advances and review the knowledge on the identification of p38MAPK substrates, functions, and regulation; mechanisms underlying the role of p38MAPK in malignant transformation and other pathologies; and therapeutic opportunities associated with regulation of p38MAPK activity.